Flexible Helping Behaviour in the Azure-Winged Magpie - Valencia-Ruíz, Juliána; De la Cruz, Carlos; González, Beatriz (Blackwell Verlag, 2003)
Helping to rear the offspring of others may be a way for younger birds to gain access to future reproduction especially when turnover of breeding opportunities is low. However, this explanation is not applicable to cases where adults also help, or when roles shift between helpers and breeders. Over a period of 6-yr, we studied a marked population of azure-winged Magpie (Cyanopica cyanus) breeding in a non-territorial, colonial system. Magpies bred in a highly flexible cooperative system, in which individuals helped at different stages of the breeding cycle, including nest building, feeding the incubating female and feeding the young and removing the faecal sacs. On average, 50% of hatched nests were assisted by helpers-at-the-nest, and nest success appeared to be positively related to the presence of helpers. Helpers were predominantly males. Although juveniles were more likely to help, both juvenile and adult birds helped. Individual birds behaved as helpers either as a first-option or after having attempted their own breeding (second-option helpers). An individual helper may assist more than one nest during the same breeding season and in different breeding seasons. Reversals between breeder and helper roles were common in both directions, within a breeding season and between years. Helping behaviour is an option for almost any member of the colony. Therefore, hypotheses related to the enhancement of future breeding opportunities for juveniles can be discarded as general explanation of helping in this species. Although the decision to help appeared to be influenced by proximal environmental conditions hindering successful breeding, the associated benefits of helping as opposed to simply recovering for future reproduction, especially for former breeders, deserve further study
Keywords: Ornitología; Cooperative breeding; Cyanopica cyanus; Hepping behaviour